Cloud Computing and Its Influence on Business Continuity Planning - Jibril, Ishmael (Journal of Technology and Systems, 2024)
Purpose: The general objective of the study was to investigate cloud computing and its influence on business continuity planning. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to cloud computing and its influence on business continuity planning. Preliminary empirical review revealed that cloud computing had significantly enhanced business continuity planning by providing increased scalability, flexibility, and cost-efficiency. The integration of cloud technologies into continuity strategies allowed organizations to manage disruptions more effectively and ensure operational resilience. Despite these benefits, challenges such as security concerns and integration issues were identified. Organizations needed to address these challenges by implementing robust security measures and aligning cloud solutions with existing continuity frameworks. Overall, cloud computing proved to be a valuable asset in supporting business continuity, provided that security and integration issues were properly managed. Unique Contribution to Theory, Practice and Policy: The Resource Based View Theory, Contingency Theory and Dynamic Capabilities Theory may be used to anchor future studies on cloud computing and its influence on business continuity planning. The study recommended several key actions for optimizing cloud computing's role in business continuity planning. Organizations were advised to enhance security measures by adopting advanced encryption and conducting regular audits. Developing comprehensive integration plans to align cloud solutions with existing frameworks was also suggested. Additionally, selecting cloud providers based on rigorous criteria and investing in staff training were emphasized as crucial for effective utilization. Regular reviews of continuity plans and collaboration with providers on compliance were recommended to ensure ongoing effectiveness. Finally, leveraging hybrid cloud models was suggested to balance the benefits of public and private clouds, optimizing continuity strategies.